Corporate Governance: Panting to Keep up with Scams - Ahamed, Naseem (Prabandhan: Indian Journal of Management, 2015)
India's top notch IT solutions provider "Satyam Inc," the recipient of the Golden Peacock Award for best corporate governance practices collapsed after its Chairman declared high level mismanagement with the company's accounts and the involvement of stewards of the company. Enron's debacle took the entire Wall Street by a sense of shock and disbelief. People found it difficult to believe as to how come such a behemoth corporation disappeared overnight. Worldcom, crushed by its $41 billion debt load, made its filing in the Southern District of New York. With $107 billion in assets, WorldCom's bankruptcy is the largest in United States history, dwarfing that of Enron Corp. In June 2005, Dennis Kozlowski, CEO of Tyco Electronics was convicted of misappropriating more than $400 million of Tyco's corporate funds. He is currently serving at least 8 years and 4 months at the Mid-State Correctional Facility in Marcy, New York. HealthSouth Scandal (2003), Freddie Mac (2003), American Insurance Group (2005), and Lehman Brothers (2008) are some of the corporate scandals that rocked the corporate world and shattered investors' confidence. The study highlighted prominent characteristics of different corporate governance models in action around the world, their salient features, and whether convergence is in the offing for these models. It also illustrated three different instances of corporate governance failure in companies based in different governance models following countries.